Researching researchers: exploring the challenges of conducting research during a pandemic - Onyinyechi Onuoha; Diane Lorenzetti; Jacqueline Pearson; Bernice Lee; Tanya Beran (Health Psychology Report)
Background Research assistants (RAs) are vital for the successful completion of research. When data collection and recruitment are dis-rupted, like during the COVID-19 pandemic and accompanying restrictions, the effects on RAs attempting to conduct re-search are unclear.